Demographic determinants of accounting students' ethical sensitivity ( A Survey Study on Students of the Accounting Department at the Faculty of Economics at Tishreen University) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The research aimed to explore the ethical sensitivity of accounting students at Tishreen University, and to study the impact of some demographic determinants on it, namely gender, age, place of origin, academic performance, and current academic year. To achieve the research objectives, hypotheses were developed based on the literature review of previous studies, then a survey was conducted using a questionnaire to collect the data necessary to test the hypotheses.  The questionnaire was distributed to accounting student in third and fourth years at the Faculty of Economics at Tishreen University.  139 acceptable responses were received. The data was transcribed and analyzed using SPSS. Descriptive statistics were relied upon to explore the ethical sensitivity of accounting students. And  the Independent Samples Test and the Simple Linear Regression were relied upon to test the hypotheses related to the determinants of ethical sensitivity, after the data had been explored and the conditions of the two aforementioned tests had been verified.The results showed that the ethical sensitivity of accounting students at the Faculty of Economics at Tishreen University is within the average range (middle), and that fourth-year students are more ethically sensitive than third-year students, meaning that the academic year has a statistically significant effect on students’ ethical sensitivity and that students’ progress in the academic years is within Accounting specialization increases their ethical sensitivity.  As for the other studied determinants (gender, age, place of origin, academic performance), they do not have a statistically significant effect on the ethical sensitivity of accounting students at Tishreen University.